2009
DOI: 10.3928/01484834-20090615-06
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating Simulation in Nursing Education: Beyond the Human Patient Simulator

Abstract: The human patient simulator or high-fidelity mannequin has become synonymous with the word simulation in nursing education. Founded on a historical context and on an evaluation of the current application of simulation in nursing education, this article challenges that assumption as limited and restrictive. A definition of simulation and a broader conceptualization of its application in nursing education are presented. The need for an ideological basis for simulation in nursing education is highlighted. The cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 65 publications
0
57
0
3
Order By: Relevance
“…The study fit into a historical-social paradigm (5) , used written (letters, course-packs, manuals) and photographic documents as primary sources, and the following secondary sources: textbooks, master's theses, doctoral dissertations and journal articles focusing on teaching about the theme (3,(6)(7)(8)(9)(10)(11)(12)(13) . To respond to the goal and compose the material, a work plan was elaborated, including the identification and location of the sources.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study fit into a historical-social paradigm (5) , used written (letters, course-packs, manuals) and photographic documents as primary sources, and the following secondary sources: textbooks, master's theses, doctoral dissertations and journal articles focusing on teaching about the theme (3,(6)(7)(8)(9)(10)(11)(12)(13) . To respond to the goal and compose the material, a work plan was elaborated, including the identification and location of the sources.…”
Section: Methodsmentioning
confidence: 99%
“…It is mainly through emerging concerns with care humanization and the assertion of bioethical and legal thinking that some of the strategies used for decades in students' learning of technical procedures start to be reconsidered and questioned, mainly those procedures in which the other person (patient or fellow student) is the practical learning object (3) .…”
Section: The Ethical-legal Justificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Video-facilitated debriefing has been reported in recent experimental studies [2][3][4][5][6][7], which have 1 2 reported inconsistent results. Grant and colleagues [3] concluded that video-facilitated simulation feedback is potentially useful in increasing desirable clinical behaviours in a simulated environment.…”
Section: Introductionmentioning
confidence: 98%